2022
DOI: 10.1097/won.0000000000000856
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Foot Ulceration on All-Cause and Cardiovascular Mortality in Diabetic Patients

Abstract: The NCPD test for this article is available online only at the journal website, jwocnonline.com, and the test can be taken online at NursingCenter.com.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…While individuals with regulated DM can expect to live as long as a person without the condition, persons with poorly controlled diabetes may experience life-threatening complications such as diabetic foot ulcers (DFUs), decreased productivity, reduced health-related quality of life, and premature death 2,3. In addition, a recent retrospective case-control study reported that individuals with DFU have high risk for all-cause of and cardiac-related deaths than a match group of individuals with DM alone 4…”
Section: Introductionmentioning
confidence: 99%
“…While individuals with regulated DM can expect to live as long as a person without the condition, persons with poorly controlled diabetes may experience life-threatening complications such as diabetic foot ulcers (DFUs), decreased productivity, reduced health-related quality of life, and premature death 2,3. In addition, a recent retrospective case-control study reported that individuals with DFU have high risk for all-cause of and cardiac-related deaths than a match group of individuals with DM alone 4…”
Section: Introductionmentioning
confidence: 99%
“…The result of assessment of risk of bias is presented in Table S2. Twenty‐three studies 9‐31 had a low risk of bias, and five studies 32‐36 had a moderate risk of bias. Six studies were identified as having a serious risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…Kaplan–Meier was used to describe the survival of DFU in 28 of the included studies 9,10,12‐21,23‐25,27,29‐38,40,41 . Of these studies, the number at risk and survival proportions could be estimated in 27 studies 9,10,12‐21,23‐25,27,29‐31,33‐38,40,41 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations